2017
DOI: 10.1097/yct.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Adjunctive Θ Burst Repetitive Transcranial Magnetic Stimulation to Right Inferior Parietal Lobule in Schizophrenia Patients With First-Rank Symptoms

Abstract: This study fails to demonstrate whether or not adjunctive cTBS to right inferior parietal lobule could significantly alleviate FRS. We also fail to provide evidence for whether this protocol has any effect on brain-derived neurotrophic factor levels, self-monitoring function, and right hemispheric γ oscillations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this study, there was no significant efficacy of active cTBS over sham, despite a significant clinical amelioration of auditory hallucinations in both groups. More recently, a study by Tikka et al81 recruited 20 patients and examined the same paradigm as Koops et al80 but targeting the right inferior parietal lobe; the results led to the same conclusion of a lack of superiority of active cTBS over sham.…”
Section: Introductionmentioning
confidence: 87%
“…In this study, there was no significant efficacy of active cTBS over sham, despite a significant clinical amelioration of auditory hallucinations in both groups. More recently, a study by Tikka et al81 recruited 20 patients and examined the same paradigm as Koops et al80 but targeting the right inferior parietal lobe; the results led to the same conclusion of a lack of superiority of active cTBS over sham.…”
Section: Introductionmentioning
confidence: 87%
“…In this study, the severity of depression was measured using HAM-D 12 and Beck Depression Inventory (BDI) 19 . Concomitant anxiety symptoms were assessed by Hamilton Anxiety Rating Scale (HAM-A) 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Intensive cTBS was chosen as the "inhibitory protocol" citing its more robust inhibitory actions on the cortical excitability than the other low-frequency rTMS. 12 An ensuing objective of our study was to find out the cTBS effects on concomitant anxiety, sexual function, and quality of life in acute-phase bipolar depression subjects as compared with placebo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Previous studies have indicated that the theta burst stimulation (TBS), a highfrequency rTMS, is a safe procedure with minor adverse effects. 22,23 A more recent and efficient form of TBS is intermittent theta burst stimulation (iTBS), which has shown faster and longer-lasting poststimulation effects. 24 Notably, iTBS can create long-term effects by inducing long-term forms of synaptic plasticity, which are longterm potentiation and long-term depression.…”
mentioning
confidence: 99%